Erratum: Population dynamics of western gorillas at Mbeli Bai (PLoS ONE (2022) 17:10 (e0275635) DOI: 10.1371/journal.pone.0275635) - Robbins, Andrew M.; Manguette, Marie L.; Breuer, Thomas; Groenenberg, Milou; Parnell, Richard J.; Stephan, Claudia; Stokes, Emma J.; Robbins, Martha M. (PLoS ONE, 2022)
There are errors in the author affiliations. The correct affiliations are as follows: Andrew M. Robbins1, Marie L. Manguette1,2, Thomas Breuer2,3, Milou Groenenberg2, Richard J. Parnell4, Claudia Stephan5,6,7, Emma J. Stokes4, Martha M. Robbins1 1 Department of Primatology, Max Planck Institute for Evolutionary Anthropology, Deutscher Platz 6, 04103 Leipzig, Germany, 2 Mbeli Bai Study, Wildlife Conservation Society Congo Program, B.P. 14537, Brazzaville, Congo, 3 World Wide Fund for Nature, Reinhardtstrasse 18, 10117 Berlin, Germany, 4 Wildlife Conservation Society, Global Conservation Program, 2300 Southern Boulevard, Bronx, NY, 10460, USA, 5 Wildlife Conservation Society- Congo Program, Republic of Congo, 6 Nouabalé-Ndoki Foundation, Republic of Congo, 7 Division of Developmental Biology, Friedrich-Alexander University Erlangen, Germany. The publisher apologizes for the errors.
CRIS-Team Scopus Importer:2024-12-16